Photocuring bioglass, bioglass bracket and preparation method of photocuring bioglass bracket
By preparing the photocured bioglass precursor and calcium and phosphorus salt, the problems of complex 3D printing process and cumbersome coating preparation are solved, and the process is simplified and the mechanical properties and bone repair effect of the bioglass scaffold are improved.
Patent Information
- Application Number
- CN202310785339.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-29
- Publication Date
- 2024-12-31
AI Technical Summary
In the prior art, the 3D printing process of bioglass is complex and difficult to ensure channel connectivity. The preparation process of bioglass coating is complicated and lacks convenient photocrosslinked SiO2-CaO-P2O5 bioglass materials.
Photocured bioglass precursors are prepared by dissolving SiO2, CaO and P2O5 precursors and reacting under acid medium, removing the solvent, and mixing them with calcium and phosphorus salts, and dried and sintered by 3D printing or filling into a porous scaffold. , realize the preparation of photocured bioglass scaffolding.
The preparation process of bioglass stents is simplified, and the good interface combination of calcium and phosphorus salts and bioglass is achieved, which improves mechanical properties and bone repair effects, promotes vascular regeneration, and reduces process complexity.
Smart Images

Figure HDA0004312118990000011 
Figure HDA0004312118990000012 
Figure HDA0004312118990000013
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new materials, and in particular to a bioglass and a bioglass support and a preparation method thereof. Background Art
[0002] Bioactive glass is a synthetic biomaterial. Because some of its ingredients can be converted into inorganic salts of bone tissue and have rapid degradation properties, it exhibits good bioactivity and bone repair properties, making it a good material for bone tissue repair. In order to make bioglass exhibit better biological properties, it is usually prepared into a porous scaffold to ensure the metabolism and conversion of the material in the body. Currently, common methods for preparing porous bioglass scaffolds include PU sponge grouting, 3D printing and other processes. However, the conventional PU grouting method is difficult to ensure complete connectivity of the pores and the process is complicated; in comparison, 3D printed bioglass scaffolds can obtain better pore connectivity, but there is still a problem of complex processes. Therefore, it is particularly necessary to develop a bioglass that is easy to use for 3D printing and bonding other inorganic biomaterials in 3D printing.
[0003] The current 3D printed bioglass scaffolds include bioglass synthesis → drying → sintering → crushing → dispersion in the forming agent → 3D printing → drying → sintering to remove the forming agent, which is a cumbersome process; at the same time, for some scaffolds with bioglass coatings, it is also necessary to first disperse the bioglass in the forming agent and apply it to the surface of the scaffold, and then dry and sinter, which is also a relatively complicated process. Therefore, the development of a new type of photo-crosslinkable SiO2-CaO-P2O5 bioglass is an urgent problem to be solved in current research. Summary of the invention
[0004] In view of the problems existing in the prior art, the first aspect of the present invention provides a method for preparing a photocurable bioglass precursor, which is characterized by comprising the following steps:
[0005] 1) dissolving a SiO2 precursor, a CaO precursor and a P2O5 precursor in a solvent to obtain a first solution;
[0006] 2) adding an acid to the first solution obtained in step 1) to react to obtain a second solution;
[0007] 3) removing the solvent from the second solution obtained in step 2) to obtain a photocurable bioglass precursor.
[0008] Preferably, the step 1) further comprises a template, and the template is dissolved in a solvent.
[0009] Preferably, the template is selected from one or more of F127, F108, P123, P105, and Poloxamer 338.
[0010] F127 is also known as Poloxamer 407, which is Polyethylene-polypropylene glycol. It is a triblock copolymer of polyoxyethylene polyoxypropylene ether. Its Chinese name is poloxamer, polyether or polyoxyethylene polyoxypropylene ether. Its molecular formula is H(C2H4O) x (C3H6O) y (C2H4O) z OH is a new type of high molecular weight nonionic surfactant, which is often used to enhance the water solubility of dyes and improve the cell permeability of fat-soluble dyes. In addition, Pluronic F-127 is also often used to separate membrane proteins and treat the surface of materials to change their properties, such as reducing the nonspecific adsorption of proteins or cells on the surface of materials.
[0011] F108 is a light yellow transparent liquid, slightly acidic, and can form latex in water. It is used to disperse pigments and fillers in oil black, paints, and coatings, shorten grinding time, prevent the aggregation and coarsening of pigment and filler particles, and has an anti-settling effect. It can ionize itself into charged groups with various structures to improve the wettability of pigments, prevent pigments and fillers in coatings from sinking to the bottom and agglomerating, and facilitate redispersion.
[0012] P123 (Aldrich, EO20PO70EO20, Ma=5800) is a nonionic surfactant that can be used as a template agent in the synthesis of SBA-15.
[0013] P105 surfactant is a polyethylene oxide (PEO)-polypropylene oxide (PPO)-polyethylene oxide (PEO) copolymer. It has two hydrophilic groups connected to a central hydrophobic group, which can self-assemble into micelle clusters in aqueous solution.
[0014] Poloxamer is a new type of polymer emulsifier, a copolymer of polyoxyethylene and polyoxypropylene. Poloxamer 338 is hydrophilic and can be used as an oil-in-water (O / W) emulsifier and surfactant --- the oil component is evenly dispersed in water in the form of fine liquid droplets to form an emulsion or suspension.
[0015] Preferably, at least one of the following technical features is included:
[0016] 11) In step 1), the SiO2 precursor includes a silicic acid source and a silane coupling agent with a double bond;
[0017] 12) In step 1), the CaO precursor is selected from one or more of Ca(NO3)2.4H2O, CaCl2, CaCO3, (CH3COO)2Ca·H2O;
[0018] 13) In step 1), the P2O5 precursor is selected from one or more of trimethyl phosphate, triethyl phosphate, tripropyl phosphate, and (NH4)2HPO4;
[0019] 14) In step 1), the solvent is selected from one or more of ethanol, methanol, acetone, dimethyl sulfoxide, and isopropanol;
[0020] 15) In step 1), the molar ratio of the SiO2 precursor, the CaO precursor and the P2O5 precursor is (2.40-5.75):(0.21-1.70):(0.10-0.44);
[0021] 16) In step 1), the molar ratio of the solvent to the SiO2 precursor is 20-60, for example, 10-30, 30-40, 40-50, 50-60.
[0022] 21) In step 2), the acid is selected from one or more of hydrochloric acid, nitric acid, formic acid, and acetic acid; the acid is added to promote the hydrolysis of tetraethyl silicate and the silane coupling agent.
[0023] 22) In step 2), the acid is added to a pH value of less than 2, so that tetraethyl silicate and the silane coupling agent are hydrolyzed and grafting occurs.
[0024] 23) In step 2), the reaction temperature is 30-80°C to increase the reaction speed while avoiding double bond crosslinking, for example, it can be 30-40°C, 40-50°C, 50-60°C, 60-70°C, 70-80°C.
[0025] 24) In step 2), the reaction time is 24-48 hours, firstly to allow the tetraethyl silicate to be completely hydrolyzed, and secondly to allow the silane coupling agent to be fully grafted. For example, it can be 24-30 hours, 30-36 hours, 36-42 hours, or 42-48 hours.
[0026] 25) In step 2), the reaction is carried out in an inert gas. Placing the reaction system in an inert gas environment with an inert gas can reduce oxidation of the bioglass surface and reduce the effect of oxygen on the properties of the bioglass.
[0027] 31) In step 3), the method for removing the solvent is rotary evaporation;
[0028] 32) In step 3), the removed solvent accounts for 80-90% of the total solvent mass;
[0029] 33) In step 3), the storage temperature of the bioglass precursor is less than 20°C. The lower storage temperature is to reduce the reactivity of double bonds, and avoiding light is to avoid double bond cross-linking.
[0030] 34) In step 3), the bioglass precursor is stored in a light-proof environment.
[0031] Preferably, at least one of the following technical features is included:
[0032] 111) In feature 11), the silicate source is selected from one or more of tetraethyl orthosilicate, methyl silicate, ethyl silicate, and sodium silicate;
[0033] 112) In feature 11), the silane coupling agent with a double bond is selected from one or more of 3-(isobutylacryloxy)propyltrimethoxysilane, allyltriethoxysilane, 3-trimethoxysilane propyl acrylate, 3-(methacryloxy)propyltrimethoxysilane, methacryloxypropyltriethoxysilane, O-(vinyloxybutyl)-N-(triethoxysilylpropyl)urethane, and 5-hexenyltrimethoxysilane, and the silicate source in the SiO2 precursor and the silane coupling agent with a double bond can be grafted.
[0034] For example: The grafting process of tetraethyl orthosilicate and 3-(isobutyleneoxy)propyltrimethoxysilane is as follows: Fig.13 shown.
[0035] 113) In feature 11), the molar ratio of the silicate to the silane coupling agent with double bonds is 9 / 1-1 / 9; and the total molar amount thereof conforms to the molar ratio of the SiO2-CaO-P2O5 precursor described in claim 3;
[0036] 141) In feature 14), the solvent is anhydrous ethanol;
[0037] 151) In feature 15), the mass ratio of the SiO2 precursor, the CaO precursor and the P2O5 precursor is (5-12):(0.5-4):(0.2-0.8);
[0038] 231) In feature 23), the reaction temperature is 30-45°C, for example, it can be 30-35°C, 35-40°C, 40-45°C.
[0039] 251) In feature 25), the inert gas is selected from nitrogen or argon;
[0040] 321) In step 31), the temperature of the rotary evaporation is less than 50°C. Preferably, the temperature of the rotary evaporation is 30-50°C, because too high a temperature will destroy the grafted double bonds and cause photocuring failure. For example, it can be 30-35°C, 35-40°C, 40-45°C, or 45-50°C.
[0041] A second aspect of the present invention provides a photocurable bioglass precursor, which is prepared by the above-mentioned method for preparing the photocurable bioglass precursor.
[0042] A third aspect of the present invention provides a method for preparing a photocurable bioglass slurry, comprising mixing the above-mentioned photocurable bioglass precursor with calcium phosphate.
[0043] Calcium phosphate is introduced into the bioglass precursor. During the sintering process, the Ca content of the calcium phosphate particles increases. 2+ , P 5+ Doping in the Si-O tetrahedron of the bioglass precursor can improve the mechanical strength, regulate the degradation performance, and achieve good bonding between the particles and the bulk interface.
[0044] Preferably, at least one of the following technical features is included:
[0045] A1) the mass ratio of the photocurable bioglass precursor to the calcium phosphate salt is 1-5:9-5;
[0046] A2) The preparation method of the calcium phosphate salt is: mixing a solution containing a soluble calcium salt with a solution containing a phosphate, adjusting the pH to alkaline, performing a hydrothermal reaction, washing, and drying.
[0047] Preferably, at least one of the following technical features is included:
[0048] A21) the soluble calcium salt is selected from one or more of calcium nitrate and calcium chloride;
[0049] A22) the phosphate is selected from one or more of diammonium hydrogen phosphate, disodium hydrogen phosphate, and dipotassium hydrogen phosphate;
[0050] A23) the solvents of the solution containing the soluble calcium salt and the solution containing the phosphate are respectively deionized water;
[0051] A24) the molar ratio of the soluble calcium salt to the phosphate is 1.5 / 1-1.67 / 1;
[0052] A25) stirring after adjusting the pH to alkaline;
[0053] A26) The pH is 10-13, for example, 10-11, 11-12, 12-13.
[0054] A27) the substance for adjusting pH is one or more of ammonia water, sodium oxide and potassium hydroxide;
[0055] A28) the temperature of the hydrothermal reaction is 80-200°C;
[0056] A29) The time of the hydrothermal reaction is 10-48 h, for example, 10-15 h, 15-20 h, 20-25 h, 25-30 h, 30-35 h, 35-40 h, 40-45 h, 45-48 h.
[0057] A fourth aspect of the present invention provides a photocurable bioglass slurry, which is prepared according to the above-mentioned method for preparing the photocurable bioglass slurry.
[0058] A fifth aspect of the present invention provides a photocurable bioglass scaffold, comprising the above-mentioned bioglass precursor or the above-mentioned photocurable bioglass slurry.
[0059] The sixth aspect of the present invention provides a method for preparing a photocured bioglass scaffold, wherein the bioglass precursor or the photocured bioglass slurry described in the claim is 3D printed or filled into other porous scaffolds, and then dried and sintered to obtain the photocured bioglass scaffold.
[0060] Preferably, at least one of the following technical features is included:
[0061] B1) When the 3D printing or filling into other porous scaffolds, it also includes adding a photoinitiator and irradiating with light;
[0062] B2) The drying temperature is 80-150°C, for example, 80-90°C, 90-100°C, 100-110°C, 110-120°C, 120-130°C, 130-140°C, 140-150°C.
[0063] B3) the sintering temperature is 400-1000°C;
[0064] B4) The sintering time is 2-12 hours, for example, 2-4 hours, 4-6 hours, 6-8 hours, 8-10 hours, 10-12 hours.
[0065] Preferably, at least one of the following technical features is included:
[0066] B11) In feature B1), the mass ratio of the amount of the photoinitiator added to the amount of the bioglass precursor is 0.01-20;
[0067] B12) In feature B1), the photoinitiator is selected from one or more of I2959 and LAP;
[0068] B13) In feature B1), the wavelength of the light is 360-405 nm;
[0069] B31) In feature B3), the sintering temperature is 400-800°C.
[0070] Initiator I2959 is a highly efficient non-yellowing UV initiator used to initiate UV polymerization reactions in unsaturated prepolymer systems. It is particularly suitable for low-odor, water-based acrylic and unsaturated polyester resins. The active hydroxyl groups of Chemicalbook in the photoinitiator 2959 molecule make it easy to react with unsaturated resins. It is suitable for conventional UV systems. Since the hydroxyl functional groups in its molecules improve the solubility of photoinitiator 2959 in water-based coating formulations, it is suitable for water-based UV formulations.
[0071] LAP is a water-soluble, cell-compatible photoinitiator for the polymerization of hydrogels or bio-inks. This photoinitiator is more useful for biological applications than Irgacure 2959 because it has a higher water solubility, a polymerization rate at 365nm light, and an absorbance at 400nm, allowing polymerization with visible light.
[0072] The present invention has the following beneficial effects:
[0073] 1) Compared with the existing preparation process, the process of the present invention has the advantage that the bioglass scaffold can be prepared once by 3D printing / mixing, etc., without the need for complicated repeated slurry preparation-sintering and other processes. At the same time, it can achieve a good interface bonding between calcium phosphate and bioglass to achieve the purpose of strengthening.
[0074] 2) Based on the traditional bioactive glass, the present invention partially replaces the silicon source with a silane coupling agent with double bonds to prepare light-cured bioglass.
[0075] 3) The present invention can change the size of the pores in the photocurable bioglass precursor or the photocurable bioglass scaffold by adjusting the amount of the template, which is beneficial to the loading of active factors.
[0076] 4) The light-cured bioglass in the present invention has good mechanical properties, which matches the cancellous bone of the human body. It is more than 10 times better than ordinary bioglass scaffolds and has an excellent effect of promoting angiogenesis in the bone repair process. BRIEF DESCRIPTION OF THE DRAWINGS
[0077] Figure 1 The infrared spectra of the bioglass and the traditional active glass in Example 1 of the present invention, wherein PBG is the bioglass precursor synthesized in Example 1, and BG is the traditional active bioglass.
[0078] Figure 2 The NMR spectra of the bioglass and traditional active glass in Example 1 of the present invention, wherein PBG is the bioglass precursor synthesized in Example 1, and BG is the traditional active bioglass.
[0079] Figure 3: The NMR spectra of the bioglass and the traditional active glass in Example 2 of the present invention, G' represents the elastic modulus of the photocured bioglass precursor, and G" represents the viscous modulus of the photocured bioglass precursor.
[0080] Figure 4 This is a rendering of the bioglass precursor after light curing in Example 3 of the present invention.
[0081] Figure 5 The surface morphology of the support after 3D printing in Example 3 of the invention Figure 1 .
[0082] Figure 6 The surface morphology of the support after 3D printing in Example 3 of the invention Figure 2 .
[0083] Figure 7 This is a diagram of the bioglass support after sintering in Example 6 of the present invention.
[0084] Figure 8 This is a morphology diagram of hydroxyapatite particles in Example 7 of the present invention.
[0085] Fig. 9 This is a diagram of the printing process of the light-cured bioglass / calcium phosphate composite material scaffold in Example 8 of the present invention.
[0086] Fig.10 This is the appearance and structure diagram of the light-cured bioglass / calcium phosphate composite material scaffold in Example 8 of the present invention.
[0087] Fig.11 This is a test diagram of the compression performance of the bioglass / calcium phosphate composite material scaffold in Example 8 of the present invention.
[0088] Fig.12 This is a diagram showing the effect of the light-cured bioglass / calcium phosphate composite material scaffold in Example 8 of the present invention in promoting angiogenesis during bone repair.
[0089] Fig.13 This is a grafting principle diagram of tetraethyl orthosilicate and 3-(isomethacryloyloxy)propyltrimethoxysilane in the present invention. DETAILED DESCRIPTION
[0090] The following is a description of the implementation of the present invention by means of specific embodiments. Those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification.
[0091] See also Figures 1 to 13. It should be noted that the structures, proportions, sizes, etc. illustrated in the drawings in this specification are only used to match the contents disclosed in the specification for people familiar with this technology to understand and read, and are not used to limit the limiting conditions for the implementation of the present invention, so they have no substantial technical significance. Any modification of the structure, change in the proportional relationship, or adjustment of the size should still fall within the scope of the technical content disclosed by the present invention without affecting the effects and purposes that can be achieved by the present invention. At the same time, the terms such as "upper", "lower", "left", "right", "middle" and "one" quoted in this specification are only for the convenience of description, and are not used to limit the scope of the implementation of the present invention. Changes or adjustments in their relative relationships should also be regarded as the scope of the implementation of the present invention without substantially changing the technical content.
[0092] Example 1
[0093] Synthesis of Photo-crosslinked SiO2-CaO-P2O5 Bioglass
[0094] 1) 5.76 g of calcium nitrate tetrahydrate and 1.67 mL of triethyl phosphate were sequentially dissolved in 360 g of ethanol. After the calcium nitrate tetrahydrate and triethyl phosphate were completely dissolved, 30.26 mL of tetraethyl orthosilicate and 12.49 mL of 3-(methacryloyloxy)propyltrimethoxysilane were added to the above solution at once to obtain a first solution;
[0095] 2) adding 10 mL of 1 M nitric acid to the first solution obtained in step 1), and reacting at 40 degrees for 24 hours to obtain a second solution;
[0096] 3) The second solution obtained in step 2) is removed from about 330 g of the solvent ethanol at 45° C. under negative pressure to obtain a bioglass precursor 1.
[0097] like Figure 1 Infrared spectrum 1718.2cm -1 The absorption peak at is the double bond peak. Figure 2 The displacements at 5.58ppm and 6.15ppm in NMR are the characteristics of double bonds, indicating that double bonds are grafted onto the molecular chains of the obtained bioglass slurry, giving it the ability to cure under ultraviolet light.
[0098] Example 2
[0099] Synthesis of Photo-crosslinked SiO2-CaO-P2O5 Bioglass
[0100] The specific steps are as follows:
[0101] 1) Dissolve 5.76 g of calcium nitrate tetrahydrate and 1.67 mL of triethyl phosphate in 360 g of ethanol in sequence. After the calcium nitrate tetrahydrate and triethyl phosphate are completely dissolved, add 20.10 mL of tetraethyl orthosilicate and 20.81 mL of 3-(trimethoxysilyl)propyl acrylate to the above solution at one time to obtain a first solution;
[0102] 2) Add 6 mL of 1 M hydrochloric acid to the first solution obtained in step 1), and react at 40 °C for 24 h to obtain a second solution;
[0103] 3) Remove about 320 g of the solvent ethanol from the second solution obtained in step 2) at 45 °C under negative pressure to obtain a bioactive glass precursor 2.
[0104] The photocurable bioactive glass precursor in the present invention cures rapidly under ultraviolet light irradiation and cures within 5 s. As Figure 3 shown, after the bioactive glass precursor is irradiated with light, both G' and G" increase rapidly, and the change from G'<G" to G'>G" indicates that the slurry cures.
[0105] Example 3
[0106] Preparation of SiO2-CaO-P2O5 bioactive glass scaffold
[0107] 1) Slurry preparation: Weigh 0.1 g of photoinitiator LAP and dissolve it in 10 g of the bioactive glass precursor prepared in Example 1 above, and then transfer it to the printer cartridge;
[0108] 2) Slurry printing: According to the designed morphology of the scaffold, adjust the printing parameters, and print the slurry mixed with the photoinitiator into a porous scaffold under 405 nm blue light exposure;
[0109] 3) Scaffold drying and sintering: Place the printed scaffold in a vacuum drying oven at 80 °C for 7 days, and then calcine it in a calcination furnace at 600 °C for 6 h to obtain the required bioactive glass scaffold 1.
[0110] The bioactive glass precursor cures rapidly after light irradiation. As Figure 4 shown, the apparent morphology of the scaffold after 3D printing is as Figure 5 , 6 shown, the porosity is 100% connected and the porosity is 70%.
[0111] Example 4
[0112] Synthesis of crosslinked mesoporous SiO2-CaO-P2O5 bioactive glass precursor
[0113] The specific steps are as follows:
[0114] 1) 5.76 g of calcium nitrate tetrahydrate, 1.56 g of triethyl phosphate and 20 g of P123 were dissolved in 400 mL of ethanol in sequence. After the calcium nitrate tetrahydrate, triethyl phosphate and P123 were completely dissolved, 20.10 g of tetraethyl orthosilicate and 18.94 g of 3-(isobutyleneoxy)propyltrimethoxysilane were added to the above solution at once to obtain a first solution;
[0115] 2) adding 6 mL of 0.5 M hydrochloric acid to the first solution obtained in step 1), and reacting at 40 degrees for 24 hours to obtain a second solution;
[0116] 3) The second solution obtained in step 2) is subjected to a negative pressure at 50 degrees to remove about 300 g of the solvent ethanol to obtain a bioglass precursor 3.
[0117] In this embodiment, P123 is a surfactant, which produces a mesoporous structure during the later sintering process.
[0118] Example 5
[0119] Synthesis of Photocrosslinked Mesoporous SiO2-CaO-P2O5 Bioglass Precursor
[0120] The specific steps are as follows:
[0121] 1) 5.76 g of calcium nitrate tetrahydrate, 1.56 g of triethyl phosphate and 24 g of F127 were dissolved in 400 mL of ethanol in sequence. After the calcium nitrate tetrahydrate, triethyl phosphate and F127 were completely dissolved, 25.94 g of tetraethyl orthosilicate and 15.15 g of 3-(methacryloyloxy)propyltrimethoxysilane were added to the above solution at once to obtain a first solution;
[0122] 2) adding 10 mL of 1 M hydrochloric acid to the first solution obtained in step 1), and reacting at 40 degrees for 24 hours to obtain a second solution;
[0123] 3) The second solution obtained in step 2) is subjected to a negative pressure at 45 degrees to remove about 300 g of the solvent ethanol to obtain a bioglass precursor 4.
[0124] Compared with Example 2, the addition of F127 brings a mesoporous structure to the bioactive glass and forms a multi-level pore structure, which is beneficial to the loading of active factors.
[0125] Example 6
[0126] Printing of Mesoporous SiO2-CaO-P2O5 Bioglass Slurry
[0127] 1) 0.1 g of LAP was dissolved in 10 g of the slurry prepared in Example 5 above, and the mixture was evenly mixed, and then transferred to the printer barrel to prepare a printable material;
[0128] 2. Slurry printing: According to the morphology of the designed scaffold, the printing parameters are adjusted, and the slurry mixed with the photoinitiator is printed into a porous scaffold under 405nm blue light exposure;
[0129] 3) Drying and sintering of the scaffold: The printed scaffold was placed in a vacuum drying oven at 80 degrees for 7 days, and then calcined in a calcining furnace at 750 degrees for 6 hours to obtain the desired bioglass scaffold 2.
[0130] like Figure 7 As shown, the mesoporous structure on the scaffold surface is conducive to the immobilization of active factors and cell adhesion.
[0131] Example 7
[0132] Hydroxyapatite preparation
[0133] The specific steps are as follows:
[0134] 1) Dissolve 0.444 g calcium chloride and 3.17 g diammonium phosphate in 25 mL respectively;
[0135] 2) adding the calcium chloride solution dropwise into the diammonium hydrogen phosphate solution, adjusting the pH value to 11 with aqueous ammonia, and then stirring at room temperature for 2 h;
[0136] 3) The reaction solution obtained in step 3) was transferred to a hydrothermal kettle, placed in an oven heated to 180 degrees, and hydrothermal for 24 hours;
[0137] 4) After the hydrothermal autoclave has cooled to room temperature, the precipitate is collected by filtration, washed to neutrality, and dried for later use.
[0138] like Figure 8 As shown, hydroxyapatite microspheres prepared by hydrothermal precipitation method have uniform particle size and spherical shape.
[0139] Example 8
[0140] Printing of light-cured bioglass / calcium phosphate composite scaffolds
[0141] 1) Slurry preparation: weigh 1 g of hydroxyapatite in Example 7 and 10 g of the bioglass precursor in Example 2, mix them evenly, then add 0.2 g of I2959, continue to stir evenly, and then transfer to the printer barrel to prepare a printable material;
[0142] 2) Slurry printing: According to the morphology of the designed scaffold, the printing parameters are adjusted, and the slurry is printed into a porous scaffold under irradiation at a wavelength of 365 nm;
[0143] 3) Stent drying and sintering: The printed stent was placed in a vacuum drying oven at 80 degrees for 7 days, and then calcined in a calcining furnace at 600 degrees for 6 hours to obtain the desired stent.
[0144] like Fig. 9 As shown in the figure, the printing process of the light-cured bioglass / calcium phosphate composite scaffold is shown. The slurry solidifies quickly after leaving the nozzle. Fig.10 As shown, the morphology and porous structure of the light-cured bioglass / calcium phosphate composite material scaffold in this embodiment are shown, and the pore size of 300-800 microns can be adjusted. Fig.11 As shown, the compression performance test results of the bioglass / calcium phosphate composite material scaffold in this embodiment show that hydroxyapatite can enhance the mechanical properties of the bioglass scaffold, and the compression strength reaches 9MPa, which matches the human cancellous bone and is more than 10 times higher than that of the bioglass scaffold. Fig.12 It shows that the photocured bioglass / calcium phosphate composite scaffold has an excellent effect in promoting angiogenesis during bone repair.
[0145] The above description is only a preferred embodiment of the present invention, and is not any formal or substantial limitation of the present invention. It should be pointed out that ordinary technicians in this technical field can make several improvements and supplements without departing from the method of the present invention, and these improvements and supplements should also be regarded as the protection scope of the present invention. Any technician familiar with this profession, without departing from the spirit and scope of the present invention, can make some changes, modifications and equivalent changes made by using the technical content disclosed above, which are equivalent embodiments of the present invention; at the same time, any changes, modifications and evolutions of any equivalent changes made to the above embodiments based on the essential technology of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a photocurable bioglass precursor, characterized in that: The following steps are involved: 1) dissolving a SiO2 precursor, a CaO precursor and a P2O5 precursor in a solvent to obtain a first solution; 2) adding an acid to the first solution obtained in step 1) to react to obtain a second solution; 3) removing the solvent from the second solution obtained in step 2) to obtain a photocurable bioglass precursor.
2. The method for preparing a light-cured bioglass precursor according to claim 1, characterized in that: The step 1) further comprises a template, which is dissolved in a solvent.
3. The method for preparing a light-cured bioglass precursor according to claim 2, characterized in that: The template agent is selected from one or more of F127, F108, P123, P105, and Poloxamer 338.
4. The method for preparing a light-cured bioglass precursor according to any one of claims 1 to 3, characterized in that: Include at least one of the following technical features: 11) In step 1), the SiO2 precursor includes a silicic acid source and a silane coupling agent with a double bond; 12) In step 1), the CaO precursor is selected from one or more of Ca(NO3)2.4H2O, CaCl2, CaCO3, (CH3COO)2Ca·H2O; 13) In step 1), the P2O5 precursor is selected from one or more of trimethyl phosphate, triethyl phosphate, tripropyl phosphate, and (NH4)2HPO4; 14) In step 1), the solvent is selected from one or more of ethanol, methanol, acetone, dimethyl sulfoxide, and isopropanol; 15) In step 1), the molar ratio of the SiO2 precursor, the CaO precursor and the P2O5 precursor is (2.40-5.75): (0.21-1.70):(0.10-0.44); 16) In step 1), the molar ratio of the solvent to the SiO2 precursor is 20-60; 21) In step 2), the acid is selected from one or more of hydrochloric acid, nitric acid, formic acid, and acetic acid; 22) In step 2), the acid is added until the pH is less than 2; 23) In step 2), the reaction temperature is 30-80°C; 24) In step 2), the reaction time is 24-48 hours; 25) In step 2), the reaction is carried out in an inert gas; 31) In step 3), the method for removing the solvent is rotary evaporation; 32) In step 3), the removed solvent accounts for 80-90% of the total solvent mass; 33) In step 3), the storage temperature of the bioglass precursor is less than 20°C; 34) In step 3), the bioglass precursor is stored in a light-proof environment.
5. The method for preparing a light-cured bioglass precursor according to claim 7, characterized in that: Include at least one of the following technical features: 111) In feature 11), the silicate source is selected from one or more of tetraethyl orthosilicate, methyl silicate, ethyl silicate, and sodium silicate; 112) In feature 11), the silane coupling agent with a double bond is selected from one or more of 3-(isomethacryloyloxy)propyltrimethoxysilane, allyltriethoxysilane, 3-trimethoxysilane propyl acrylate, 3-(methacryloyloxy)propyltrimethoxysilane, methacryloxypropyltriethoxysilane, O-(vinyloxybutyl)-N-(triethoxysilylpropyl)urethane, and 5-hexenyltrimethoxysilane; 113) In feature 11), the molar ratio of the silicate to the silane coupling agent with double bonds is 9 / 1-1 / 9; and the total molar amount thereof conforms to the molar ratio of the SiO2-CaO-P2O5 precursor described in claim 3; 141) In feature 14), the solvent is anhydrous ethanol; 151) In feature 15), the mass ratio of the SiO2 precursor, the CaO precursor and the P2O5 precursor is (5-12): (0.5-4):(0.2-0.8); 231) In feature 23), the reaction temperature is 30-45°C; 251) In feature 25), the inert gas is selected from nitrogen or argon; 321) In step 31), the temperature of the rotary evaporation is less than 50°C, preferably, the temperature of the rotary evaporation is 30-50°C.
6. A photocurable bioglass precursor, characterized in that: The photocurable bioglass precursor is prepared by the method for preparing the photocurable bioglass precursor according to any one of claims 1 to 5.
7. A method for preparing a light-cured bioglass slurry, characterized in that: The method further comprises mixing the photocurable bioglass precursor obtained according to any one of claims 1 to 5 with calcium phosphate.
8. The method for preparing the light-cured bioglass slurry according to claim 7, characterized in that: Include at least one of the following technical features: A1) the mass ratio of the photocurable bioglass precursor to the calcium phosphate salt is 1-5:9-5; A2) The preparation method of the calcium phosphate salt is: mixing a solution containing a soluble calcium salt with a solution containing a phosphate, adjusting the pH to alkaline, performing a hydrothermal reaction, washing, and drying.
9. The method for preparing the light-cured bioglass slurry according to claim 8, characterized in that: Include at least one of the following technical features: A21) the soluble calcium salt is selected from one or more of calcium nitrate and calcium chloride; A22) the phosphate is selected from one or more of diammonium hydrogen phosphate, disodium hydrogen phosphate, and dipotassium hydrogen phosphate; A23) the solvents of the solution containing the soluble calcium salt and the solution containing the phosphate are respectively deionized water; A24) the molar ratio of the soluble calcium salt to the phosphate is 1.5 / 1-1.67 / 1; A25) stirring after adjusting the pH to alkaline; A26) the pH is 10-13; A27) the substance for adjusting pH is one or more of ammonia water, sodium oxide and potassium hydroxide; A28) the temperature of the hydrothermal reaction is 80-200°C; A29) The hydrothermal reaction time is 10-48h.
10. A light-cured bioglass slurry, characterized in that: The photocurable bioglass slurry is prepared according to the method for preparing the photocurable bioglass slurry according to any one of claims 7 to 9.
11. A light-cured bioglass scaffold, characterized in that: It comprises the bioglass precursor according to claim 6 or the light-cured bioglass slurry according to claim 10.
12. A method for preparing a light-cured bioglass scaffold, characterized in that: The bioglass precursor described in claim 6 or the photocurable bioglass slurry described in claim 10 is 3D printed or filled into other porous brackets, dried and sintered to obtain the photocurable bioglass bracket.
13. The method for preparing the light-cured bioglass scaffold according to claim 12, characterized in that: Include at least one of the following technical features: B1) When the 3D printing or filling into other porous scaffolds, it also includes adding a photoinitiator and irradiating with light; B2) the drying temperature is 80-150°C; B3) the sintering temperature is 400-1000°C; B4) The sintering time is 2-12h.
14. The method for preparing a light-cured bioglass scaffold according to claim 11, characterized in that: Include at least one of the following technical features: B11) In feature B1), the mass ratio of the added amount of the photoinitiator to the bioglass precursor is 0.01-20; B12) In feature B1), the photoinitiator is selected from one or more of I2959 and LAP; B13) In feature B1), the wavelength of the light is 360-405 nm; B31) In feature B3), the sintering temperature is 400-800°C.
Citation Information
Cited By
An additive for enhancing the biological activity of photocured hydrogel and a preparation method and application thereof
CN122749897A